Using dual stable isotopes method for nitrate sources identification in Cao-E River Basin, Eastern China - Li, Jiangnan; Sun, Qianhang; Lei, Kun; Cui, Liang; Lv, Xubo (Frontiers in Environmental Science, 2023)
Excess nitrate (NO3−) of water is a worldwide environmental problem. Therefore, identifying the sources and analyzing respective contribution rates are of great importance for improving water quality. The current study was carried out to identify the potential sources of NO3− pollution in Cao-E River basin, in Eastern China. Surface water samples were collected during the dry season and wet season. Multiple hydrochemical indices, dual NO3− isotopes (δ15N–NO3− and δ18O–NO3−) and a Bayesian model (stable isotope analysis in R, MixSIAR) were applied to identify NO3− sources and estimate the proportional contributions of multiple NO3− sources. During the sampling period, nitrification was a dominant nitrogen transformation process in the study area. The results of the NO3− isotopes suggested that manure and sewage (M&S), soil nitrogen (SN) and nitrogen fertilizer (NF) were the major contributors to NO3−. Moreover, the results obtained from the MixSIAR model showed that the proportional contributions of atmospheric deposition (AD), NF, M&S and SN to NO3− were 2.82, 15.45, 44.25, 37.47% and 3.14, 23.39, 31.78, 41.69% in the dry and wet season, respectively. This study provided evidence to further understand the sources, transport, and transformation of N in Cao-E River basin, which deepens the understanding of the management of N contaminant.